Ανάλυση, συσχέτιση και αξιολόγηση τηλεπισκοπικών δεδομένων, απο δορυφόρους, μη επανδρωμένα εναέρια οχήματα και φασματοραδιόμετρα πεδίου, με εφαρμογές στην γεωργία ακριβείας - Οικονόμου, Μάριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Τοπογραφίας. Εργαστήριο Τηλεπισκόπησης, 2014)
Recent advances in remote sensing technology have allowed the efficient use of several types of sensors in order to accomplish the implementation of precision agriculture applications. In particular, such applications have been used in viticulture aiming to improve the management of the upcoming harvest. The present study focuses on the analysis, regression and evaluation of hyperspectral and multispectral data collected for aplications in precision viticulture. Data collection was planed for 5 study areas (Nemea, Aminteo, Naousa, Atalanti, Trapeza) where vineyards are cultivated, and was dated just before the harvest period (July-August) during 3 campaigns (2012-2014). Three different types of data were processed including, ground radiance data using a field spectrometer (GER 1500, Spectra Vista Corporation, 350-1050nm, 512 spectral bands), WorldView-2 satellite data (DigitalGlobe, Inc. USA), and hyperspectral camera data (Micro-Hyperspec™ VNIR A1 Series,Headwall photonics, Inc. USA).